Analysis of electrical mismatches in high-concentrator photovoltaic power plants with distributed inverter configurations. (15th July 2016) - Rodrigo, P.; Velázquez, Ramiro; Fernández, Eduardo F.; Almonacid, F.; Pérez-Higueras, P.J.
Abstract: Electrical mismatches have a larger impact in high-concentrator photovoltaic power plants than in conventional photovoltaic systems because of the narrow acceptance angles and the unavoidable self-shading between sun trackers. In this paper, a commercial point-focus Fresnel lens-based high-concentrator photovoltaic module is characterized outdoors and results of this characterization are used to develop a power plant model which allows electrical mismatch energy losses to be investigated. Different inverter configurations (micro, string and tracker-oriented inverters) are analyzed with it. This research offers an approach based on energy loss calculation rather than instantaneous power loss calculation as was done in the reviewed literature. Moreover, realistic 28.5 kWp trackers are analyzed rather than small trackers and a novel procedure for obtaining direct normal irradiance daily profiles is presented. From the simulations, it is concluded that micro and string inverters are very useful to minimize mismatch energy losses, reinforcing the conclusions previously published by Kim and Winston (2014). The coefficients obtained in this paper are expected to help in energy yield calculations without the need of using advanced electrical modeling, although it was found that the bigger the capacity of the inverters, the higher the uncertainty to establish electrical mismatch loss coefficients due to shading. Highlights: Analysis of electrical mismatches for distributed inverter schemes in HCPV plants. Electrical mismatch percentages due to module misalignment and shading are given. Micro-inverters give 1.1% (misalignment) and 0.1% (shading) energy losses. String-inverters give 2.7% (misalignment) and 0.5% (shading) energy losses. Tracker-inverters give 3.8% (misalignment) and 1.2–3.2% (shading) energy losses.